Federal Court Cases: Integrated Data Base Appellate and Civil Pending Data, 2014 ([Verlag nicht ermittelbar], 2010)
The purpose of this data collection is to provide an official public record of the business of the federal courts. The data originate from district and appellate court offices throughout the United States. Information was obtained at two points in the life of appellate and civil cases: filing and termination. The termination data (archived as separate data collections each year) contain information on both filing and terminations, while the pending data (archived as this data collection and updated annually) contain only filing information on the most recent pending cases. The unit of analysis for the appellate and civil pending data is the case.